2020
DOI: 10.1558/isla.37279
|View full text |Cite
|
Sign up to set email alerts
|

The effects of explicit pronunciation instruction on the production of second language Spanish voiceless stops

Abstract: The present study examines the effectiveness of second language explicit pronunciation instruction of adult second language (L2) learners of Spanish in a classroom setting. This study seeks to shed light on the effectiveness of teaching pronunciation while considering the level of instruction of first, second and third year students. Eighty-three learners of Spanish as an L2 were recruited to participate in a control (n = 45) or experimental (n = 38) group. From the beginning to the end of a twelve-week semest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Such instructional interventions have been tested in a number of studies, showing overall that L2 learners’ phonological knowledge can indeed be improved through instruction. This finding has held in both speech production (e.g., Bradlow, Pisoni, Akahane‐Yamada, & Tohkura, 1997; Camus, 2019; Saito, 2011, 2013) and perception (e.g., Hirata, 2004; Logan, Lively, & Pisoni, 1991), and in laboratory settings (e.g., Bradlow et al., 1997; Hirata, 2004; Logan et al., 1991; Saito, 2011) and in classroom settings (e.g., Camus, 2019; Saito, 2013; see Saito, 2012 for a review of quasi‐experimental studies of L2 pronunciation instruction). The positive effects of instruction have been observed even for notoriously difficult aspects of pronunciation such as the English /r/–/l/ contrast for L1 Japanese learners (e.g., Bradlow et al., 1997; Logan et al., 1991).…”
Section: Background Literaturementioning
confidence: 88%
“…Such instructional interventions have been tested in a number of studies, showing overall that L2 learners’ phonological knowledge can indeed be improved through instruction. This finding has held in both speech production (e.g., Bradlow, Pisoni, Akahane‐Yamada, & Tohkura, 1997; Camus, 2019; Saito, 2011, 2013) and perception (e.g., Hirata, 2004; Logan, Lively, & Pisoni, 1991), and in laboratory settings (e.g., Bradlow et al., 1997; Hirata, 2004; Logan et al., 1991; Saito, 2011) and in classroom settings (e.g., Camus, 2019; Saito, 2013; see Saito, 2012 for a review of quasi‐experimental studies of L2 pronunciation instruction). The positive effects of instruction have been observed even for notoriously difficult aspects of pronunciation such as the English /r/–/l/ contrast for L1 Japanese learners (e.g., Bradlow et al., 1997; Logan et al., 1991).…”
Section: Background Literaturementioning
confidence: 88%
“…Nowadays, several researches (ARAÚJO et al, 2010;AZEREDO SILVA, 2004;BARREIRA, 2008;COATS, 2014;GHORBANI, 2011;GORDON et al, 2013;GOSWAMI;CHEN, 2010;KENNEDY et al, 2013;KISSLING, 2012;LINTUNEN, 2013;LIPINSKA, 2013;STURM, 2013) have investigated the role of phonetics teaching on perception and production of second language (L2) and foreign language (FL) sounds. Those studies have demonstrated that phonetics teaching plays a crucial role in the development and improvement of L2/FL learners' performance in sounds perception and production.…”
Section: Resultsmentioning
confidence: 99%
“…Although learners learn a great deal through immersion in the language, they can also benefit from pronunciation instruction in language courses (e.g., Kissling, 2013, but see also Lord, 2005). Unfortunately, in most language courses, pronunciation is given limited attention (for Spanish, see Arteaga, 2000;Bartolí, 2005;Camus-Oyarzún, 2016;Elliot, 1997;Paredes García, 2013, inter alia; see also Derwing & Munro, 2005. There are several reasons for this.…”
Section: Challenges For Spanish Pronunciation Trainingmentioning
confidence: 99%